2012 IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks (WoWMoM) 2012
DOI: 10.1109/wowmom.2012.6263682
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the information spreading delay in heterogeneous mobility DTNs

Abstract: Epidemic spreading is one of the most popular bio-inspired principles, which has made its way into computer networking. This principle naturally applies to Opportunistic or Delay Tolerant Networks (DTNs), where nodes probabilistically meet their neighbors thanks to mobility. Epidemic-based algorithms are often the only choice for DTN problems such as broadcast and unicast routing, distributed estimation etc. Existing analyses of epidemic spreading in various contexts only consider specific graph geometries (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…To capture the heterogeneity of patterns, we adopt a Marked Poisson Process model of node contacts [9], [10]. In this model, the meeting times of any two nodes (i, j) follow a Poisson Process with rate 位 ij = 位p ij .…”
Section: Diffusionmentioning
confidence: 99%
“…To capture the heterogeneity of patterns, we adopt a Marked Poisson Process model of node contacts [9], [10]. In this model, the meeting times of any two nodes (i, j) follow a Poisson Process with rate 位 ij = 位p ij .…”
Section: Diffusionmentioning
confidence: 99%
“…In [11,12], the heterogeneous network model was established and analyzed. In this kind of model, the contact between nodes is based on IDD assumption.…”
Section: Related Workmentioning
confidence: 99%
“…What's more, more complex behavior between nodes was researched and proposed for the routing designing for DTNs [8]. In [11,12], experimental simulation results showed that heterogeneous model was more reliable and reasonable than the IID assumption based models.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Common for all these works is that they assume homogeneous system. Heterogeneity is introduced by separating network nodes into multiple mobility classes in [9], [13], or modeling completely heterogeneous networks, as in [11]. However, it is debatable whether using these analytic models gives enough insight over simulations to account for their complexity.…”
Section: Related Workmentioning
confidence: 99%